Influence of Substrate and Length on the Ability of Root Segments Cuttings of Amblygonocarpus andongensis (Welw. ex Oliv.) Exell & Torre to Regenerate - De Dieu, Wangbitching Jean; Yougouda, Hamawa; Guidawa, Fawa; Jean-Baptiste, Binwe; Rodrigue, Madi Ameti Damba; Hervé, Apana Ewodo Joseph; Parfait, Wamba Sopgou Dongmo; Zéphirin, Oumarou Haman; Herbert, Abdoulaye; Marie, Mapongmetsem Pierre (Discoveries in Agriculture and Food Sciences, 2024)
The Guinean Savanah Highlands of Adamawa is replete with multipurpose tree species, among which Ambligonocarpus andongensis is particularly noteworthy. This species is widely known and appreciated by the local population. Despite its importance, it remains in the wild and is subjected to overexploitation. The objective of the present study is to evaluate the effect of substrate and length of cuttings on the budding and rooting capacity of this species.The experimental design was a split-plot with three replications. The main treatment comprised three substrates (sand/sawdust, black soil/sawdust, black soil), while the sub-treatments were represented by three lengths of root segments cuttings (RSC) (10,15,20cm). The experimental unit consisted of 10 cuttings. Following 37 weeks of monitoring, the budding rates demonstrated fluctuations, with the rates of 12.22 ± 10.92% observed in black soil and 32.22 ± 18.55% in sand/sawdust mixture. The analysis of variance indicated a significant difference between the substrate (0,005 < 0.01). For the length of cuttings, the budding rates exhibited significant fluctuations (0.001< 0.01), with the lowest rate observed for cutting of 10 cm (11.11 ± 10.86%), and the highest observed for those of 20 cm (42.22 ± 25.87%). The height of the leafy shoots revealed variations, with a mean value of 3.38 ± 3.09 cm in the black soil and a maximum value of 9.2 ± 7.10 cm in the black soil/sawdust substrate. The analysis of variance indicated a significant difference (0.03 > 0.05). The rooting rate varied significantly from 1.11±0.96% in the black soil to 12.22±12.01% in the sand/sawdust mixture (0.005 < 0.01) and for the length it also significantly fluctuated from 2.22±1.96% for cuttings of 10 cm to 15.55±13.33% for those of 20 cm (0.001 < 0.01). All these informations are important to develop scales and strategies toward the domestication of this species.